The EDUCO program, impact evaluations, and the political economy of global education reform - D. Brent Edwards, Jr.; Claudia Elizabeth Loucel Urquilla (Education Policy Analysis Archives, 2016)
During the 1990s and 2000s, a policy known as Education with Community Participation (EDUCO) not only became the cornerstone of education reform in El Salvador but also became a global education policy, one which is known for decentralizing to rural families the responsibility for hiring and firing teachers. As is shown in this paper, its rise to fame was not only a product of the particular political-economic context in which it was borne, but was also a product of the impact evaluations produced by the World Bank, which served as the evidence base through which this and other international institutions could legitimately promote the neoliberal model of community involvement represented by EDUCO. Problematically, however, a reappraisal of these impact evaluations reveals, first, that their findings and conclusions around significant effects were not warranted and, second, that the entire impact evaluation enterprise is fundamentally flawed due to the financial-political-intellectual complex out of which these studies emerged and back into which they fed as they were used to advocate for market-oriented policy solutions around the world. Thus, in addition to explaining the reform dynamics that gave rise to EDUCO, this paper (a) systematically reviews the findings and limitations of each of the six impact studies that constitute the international knowledge base around this policy, (b) reconsiders what we can reasonably claim to know about EDUCO, (c) reflects on the national and international implications of the critical review presented here, and (d) remarks on the shortcomings of—and the alternatives to—impact evaluations as a means to produce policy-relevant findings.